Carbon sequestration potential of selected seaweeds of Thikkodi, Kerala - Saranya M.S (Academy of climate change education and research, 2019)
ABSTRACT The coastal blue carbon is the carbon sequestered by mangrove, tidal marshes, seagrasses and macroalgae which account for less than 0.5% of the seabed. Unlike, other blue carbon sectors (mangroves, tidal marshes and seagrasses), the macroalgae do not have sedimentary substratum. The macroalgae are commonly known as seaweeds. The ‘seaweeds’ as the name suggest is not an unwanted plant or weed. It has an important role in the marine ecosystem by acting as a sink for carbon emissions. The present study is based on the carbon sequestration potential of selected seaweeds of Thikkodi coast, Kerala. The state of Kerala has a long coastline of about 580 km, ranking only third among all the maritime states of the country. Some of these coastline stretches are pegged with areas of seaweed resources. The Thikkodi coast (11º28’30.8” N, 75º37’04.5”E) in the Kozhikode district of Kerala is well known for its rocky intertidal coast with a luxuriant growth of seaweeds of diverse species. An extensive study of seaweeds and their species diversity was carried out for a period of one year from September 2018 to August 2019 along the Thikkodi coast of Kerala. A total of 40 species of seaweeds were recorded which belonged to 23 genera, 18 families and 14 orders. A total of 19 species belonged to Chlorophyta, while 12 species belonged to Rhodophyta and 9 species belonged to Phaeophyta. The distribution and seasonal abundance of different species along the Thikkodi coast was also studied. The biodiversity indices were studied using PRIMER (Plymouth Routines in Multivariate Ecological Research). The biodiversity indices such as Shannon-Wiener diversity (H’), Pielou’s evenness (J’), Margalef species richness (d) were calculated. The seaweeds collected from Thikkodi coast were used to carry out the carbon sequestration potential studies. While comparing the three zones, the highest value of species richness (S) was obtained in zone 1 (S=14.00), followed by zone 2 (S=8.75) and zone 3 (S=7.08). The Margalef’s index (d) which incorporates the number of individuals (N) and species (S) was the highest in zone 1 (2.10), while it was minimum in zone 3 (1.08). The equitability or individuals among the different species showed much variation between the zones and the values ranged from 0.67 (zone 2) to 0.77 (zone 1). In the present study, the Shannon Wiener Index (H’) showed wide variation between the zones ranging from the lowest value of 1.33 (zone 3) to the highest value of 1.99 (zone 1). The Simpson Index (1-Lambda’) showed variations in values ranging from 0.66 (zone 3) to 0.82 (zone 1). The experiments were conducted on selected seaweeds particularly Gracilaria corticata, Caulerpa scalpelliformis and Caulerpa peltata. Carbon dioxide was dissolved in seawater at different concentrations using a soda maker by adjusting the fizz. After determining the initial CO2, the seaweeds were incubated in 125ml light bottles under a water column of 50-60cm for 2 hours. The initial CO2 concentration (mg/l) and the CO2 utilization were examined by titrating the seawater against 0.5N Sodium hydroxide solution using Phenolphthalein indicator. The Gross Primary Production (GPP) and Net Primary Production (NPP) were also estimated. For Gracilaria corticata, the utilization efficiency increased from 33.33% to 83.33% in lower CO2 concentration of 26.4mg/l and 79.2mg/l respectively. For Caulerpa scalpelliformis, the utilization efficiency increased from 25% to 42.86% in a lower CO2 concentration of 17.6mg/l and 30.8mg/l respectively. For Caulerpa peltata, the utilization efficiency increased from 66.67% to 75% in a lower CO2 concentration of 13.2mg/l and 35.2 mg/l respectively. When the concentration of CO2was increased beyond a threshold level, the CO2 utilization efficiency decreases and cease down to zero .Same is the case for productivity. Therefore the study implies that the carbon sequestration potential of different species of seaweeds varies. The macroalgae have a greater potential to act as carbon sink and based on the sequestration potential of seaweeds, selection of different species of seaweeds can be made possible for developing Seaweed Aquaculture Beds (SABs). The SABs provide important structure in coastal ecosystem and play an incredible role in climate change mitigation aspects.